Integrating Faith and Culture: The Role of Islamic Da’wah in Shaping Sustainable Religious Tourism at Mbah Nur Walangsanga’s Shrine, Indonesia - Isni Ulul Azmi; Fachrur Rozi; Hatta Abdul Mali (Journal of Religious Studies, 2025)
Purpose: This study examines how Islamic da’wah functions as both a spiritual and socio-cultural force in developing sustainable religious tourism at Mbah Nur Walangsanga’s Shrine in Pemalang, Indonesia. The research aims to uncover how faith-based activities, community participation, and cultural preservation intertwine to create a religious tourism model that aligns with Islamic values while supporting local development. Method: Using a qualitative descriptive approach, data were collected through in-depth interviews, field observations, and document analysis. The primary informants consisted of shrine caretakers, religious leaders, and local visitors. Data interpretation employed thematic coding to connect two conceptual frameworks: the seven principles of Sapta Pesona tourism (safety, order, cleanliness, beauty, comfort, friendliness, and memorable experience) and the core elements of da’wah (preacher, audience, message, method, and impact). Findings: The results reveal that the shrine serves as an active center of religious learning and community engagement. Da’wah activities such as communal dzikr, Quran recitation, and the annual haul celebration strengthen both faith and social harmony. However, environmental management and cleanliness remain areas requiring improvement to achieve holistic sustainability. Significance: This study contributes to the growing discourse on Islamic tourism by demonstrating that da’wah can act as a cultural mechanism for sustainable destination development. It emphasizes the need for collaborative governance between local caretakers and policymakers to balance spiritual authenticity with responsible tourism practices, providing a replicable model for other faith-based heritage sites in Southeast Asia.